North American Pit Viper Envenomation - Stephen Mac; Mary Wittler (Association of American Medical Colleges, 2015)
Abstract Acute snake envenomation is an uncommon but potentially serious envenomation causing local tissue injury, hematologic derangements, and systemic effects. The purpose of this simulation is to present an acute snake envenomation case that allows residents, fellows, and other care providers to test their knowledge base and critically evaluate the management of this type of injury. The case submission contains four elements to help run the simulation. The first element is the case narrative, which includes all pertinent case information, interpretations of the case information, and anticipated case branch points. The second element is a PowerPoint presentation that contains pertinent case lab information, X-ray, and EKG to be used during the case simulation. The third element is a PowerPoint presentation that contains teaching points for the debriefing session. Finally, an evaluation form that contains recommended care actions is included. As this is an uncommon injury, most residents and fellows are not familiar with the management of this injury. The simulation was tested on both fellow physicians and residents in the emergency room to provide realistic experience. The participants were able to explore facets of the management of snake bite envenomation. They learned their own limitations in general wound care and the use of antivenom. After debriefing and going through the supplementation appendices, they expressed a general better understanding in how to take care of these potentially critical injuries.